PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN WORDWALL PADA MATERI SIKLUS - Tsalis Fitriani; Lina Novita; Santa (STKIP Subang, 2023)
Evaluation of learning is a process of collecting, analyzing, and interpreting information systematically which aims to see the level of development of students in achieving learning goals. This research is a Research and Development (R&D) using the ADDIE model (Analyse, Design, Development, Implementation, Evaluation) which aims to produce an innovative learning evaluation using wordwalls on water cycle material in class V. The research was conducted at SDN Bantarkemang 6 with a total 27 students in the 2022/2023 academic year. The research begins by analyzing the needs of teachers, curriculum, and students. Then make a design plan and develop it and try it out limited to students. The results of the validation trial stated that the evaluation of learning using wordwalls was very feasible with an assessment percentage of 95.5%. While the results of the trial were limited to fifth grade students stating that learning evaluation using wordwalls was in a very interesting category with an assessment percentage of 91.33%. Based on the results of this study it can be concluded that learning evaluation using wordwalls on water cycle material is feasible to use in the learning process.